2013
DOI: 10.1210/jc.2013-2831
|View full text |Cite
|
Sign up to set email alerts
|

Birth Defects After Early Pregnancy Use of Antithyroid Drugs: A Danish Nationwide Study

Abstract: Both MMI/CMZ and PTU were associated with birth defects, but the spectrum of malformations differed. More studies are needed to corroborate results in regard to early pregnancy shift from MMI/CMZ to PTU. New ATD with fewer side effects should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
212
2
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 243 publications
(234 citation statements)
references
References 35 publications
9
212
2
11
Order By: Relevance
“…In this study, the highest relative risk was seen for various types of abdominal wall defects (Fig. 3), followed by skin defects (aplasia cutis), digestive (oesophageal and other atresias), eye, urinary tract, respiratory (choanal atresia), and circulatory (ventricular septum) defects (57,58).…”
Section: Therapy Of Graves' Disease and The Risk Of Birth Defectsmentioning
confidence: 53%
See 3 more Smart Citations
“…In this study, the highest relative risk was seen for various types of abdominal wall defects (Fig. 3), followed by skin defects (aplasia cutis), digestive (oesophageal and other atresias), eye, urinary tract, respiratory (choanal atresia), and circulatory (ventricular septum) defects (57,58).…”
Section: Therapy Of Graves' Disease and The Risk Of Birth Defectsmentioning
confidence: 53%
“…In recent years, large studies from Japan (55, 56) and Denmark (57,58) have shown that MMI/CMZ-associated birth defects are more common than anticipated, and may affect ~1/30 of children exposed to the drug in the weeks 6-10 of pregnancy. This is considerably below 10% of the effect of thalidomide, the prime drug example of teratogenicity (59), but still enough to raise serious concern.…”
Section: Therapy Of Graves' Disease and The Risk Of Birth Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such studies, the prevalence of disease depends on the biochemical definition of thyroid disease as well as the gestational week of sampling. Similarly for register-based studies (19,20,21), the prevalence of disease will depend on the criteria applied and the available registered information. We evaluated the prevalence of thyroid dysfunction in the DNBC by redeemed prescription of thyroid medication and observed that 0.2% of the women were treated for hyperthyroidism and 0.5% for hypothyroidism in the pregnancy.…”
Section: Prevalence Of Thyroid Disease In Pregnancymentioning
confidence: 99%